An Unusual Case of Monolobar Caroli’s Disease - Anthony J Gomez; Robert J Bailey (Canadian Journal of Gastroenterology)
A 27-year-old male with recurrent upper abdominal pain was found to have a suspicious mass in the right hepatic lobe. Right hepatectomy was performed. Pathological examination and further radiological evaluation proved this to be a focal form of Caroli’s disease.